# Thread: Algebra Fail! - Simplifying squared terms.

1. ## Algebra Fail! - Simplifying squared terms.

$\displaystyle (x+1/2)^2 - (x+3/2)^2$

How does it simplify... Is there a name for term of this nature? I've forgotten.

2. Originally Posted by NeZVa
$\displaystyle (x+1/2)^2 - (x+3/2)^2$

How does it simplify... Is there a name for term of this nature? I've forgotten.
$\displaystyle (x+1/2)^2 - (x+3/2)^2$
= $\displaystyle {(x^2)+2*x*\frac{1}{2}+[\frac{1}{2}]^2} - [(x^2)+2*x*[\frac{3}{2}]+[\frac{3}{2}]^2]$

= $\displaystyle {x^2}+x+\frac{1}{4}-{x^2}-3x-\frac{9}{4}$

= $\displaystyle -2x-\frac{8}{4}$

=$\displaystyle -2x-2$

=$\displaystyle -2(x+1)$

3. Originally Posted by harish21
$\displaystyle (x+1/2)^2 - (x+3/2)^2$
= $\displaystyle {(x^2)+2*x*\frac{1}{2}+[\frac{1}{2}]^2} - [(x^2)+2*x*[\frac{3}{2}]+[\frac{3}{2}]^2]$

= $\displaystyle {x^2}+x+\frac{1}{4}-{x^2}-3x-\frac{9}{4}$

= $\displaystyle -2x-\frac{8}{4}$

=$\displaystyle -2x-2$

=$\displaystyle -2(x+1)$
Remember: $\displaystyle (a+b)^2 = {a^2}+2ab+{b^2}$

4. Originally Posted by harish21
Remember: $\displaystyle (a+b)^2 = {a^2}+2ab+{b^2}$
Thanks, I had such a brain fart.